An arid house for a xerophilic bug Nysius huttoni - Sullivan, T.E.S. (New Zealand Plant Protection, 2016)
With sensors and microprocessors becoming more affordable all the time it is now possible to build inexpensive environmental regulators for small insect colony boxes We designed and built a humidity regulator for xerophilic (dryloving) Nysius bugs Poorly ventilated insect rearing boxes can have an overly elevated humidity that can promote unwanted fungal growth especially if there is live plant material involved Air conditioned laboratories can have very low ambient humidity but the ideal humidity for an insect colony may be intermediate Direct and accurate measurement and control of humidity is now possible electronically using sensors and a fan to pump dry air into a humid space in a controlled fashion to regulate the humidity The potential exits for different sensors to be used to monitor different environmental variables and to trigger equipment to respond when an environmental threshold is reached Environmental control methods can be simple or elaborate depending on the colony requirements and budget A clock and memory card can be added to the microprocessor to record sensor data and event triggers This method has been successfully used to rear the wheat bug Nysius huttoni